MicroRNA: role in macrophage polarization and the pathogenesis of the liver fibrosis - Yu, Wen; Wang, Shu; Wang, Yangyang; Chen, Hui; Nie, Hao; Liu, Lian; Zou, Xiaoting; Gong, Quan; Zheng, Bing (Frontiers in Immunology, 2023)
Macrophages, as central components of innate immunity, feature significant heterogeneity. Numerus studies have revealed the pivotal roles of macrophages in the pathogenesis of liver fibrosis induced by various factors. Hepatic macrophages function to trigger inflammation in response to injury. They induce liver fibrosis by activating hepatic stellate cells (HSCs), and then inflammation and fibrosis are alleviated by the degradation of the extracellular matrix and release of anti-inflammatory cytokines. MicroRNAs (miRNAs), a class of small non-coding endogenous RNA molecules that regulate gene expression through translation repression or mRNA degradation, have distinct roles in modulating macrophage activation, polarization, tissue infiltration, and inflammation regression. Considering the complex etiology and pathogenesis of liver diseases, the role and mechanism of miRNAs and macrophages in liver fibrosis need to be further clarified. We first summarized the origin, phenotypes and functions of hepatic macrophages, then clarified the role of miRNAs in the polarization of macrophages. Finally, we comprehensively discussed the role of miRNAs and macrophages in the pathogenesis of liver fibrotic disease. Understanding the mechanism of hepatic macrophage heterogeneity in various types of liver fibrosis and the role of miRNAs on macrophage polarization provides a useful reference for further research on miRNA-mediated macrophage polarization in liver fibrosis, and also contributes to the development of new therapies targeting miRNA and macrophage subsets for liver fibrosis.